The Profound Influence of Lipid Composition on the Catalysis of the Drug Target NADH Type II Oxidoreductase - Albert Godoy-Hernandez (Membranes, 2021)
Lipids play a pivotal role in cellular respiration, providing the natural environment in which an oxidoreductase interacts with the quinone pool. To date, it is generally accepted that negatively charged lipids play a major role in the activity of quinone oxidoreductases. By changing lipid compositions when assaying a type II NADH:quinone oxidoreductase, we demonstrate that phosphatidylethanolamine has an essential role in substrate binding and catalysis. We also reveal the importance of acyl chain composition, specifically c14:0, on membrane-bound quinone-mediated catalysis. This demonstrates that oxidoreductase lipid specificity is more diverse than originally thought and that the lipid environment plays an important role in the physiological catalysis of membrane-bound oxidoreductases.